Evaluasi Pengelolaan Pariwisata pada Kawasan Wisata Mangrove Margomulyo berdasarkan konsep Community Based Tourism (CBT) - Nur, Muhammad; Novianti Tufail, Dwiana; Arif Nugroho, Rizky; Diyah Syafitri, Elin (Perencanaan Wilayah dan Kota, Institut Teknologi Kalimantan, 2024)
Mangrove Tourism of Margomulyo, Kecamatan Balikpapan Barat, has problems that must be fixed, namely the community around the tourist area has not all participated in promoting their tourism, the involvement of the community has not been maximized since the beginning in tourism management, so that the benefits obtained from the management of the Mangrove Tourism Area managed by the community have not been evenly distributed to all communities in the mangrove tourism area. So the goal was found in the form of evaluating the development of the management of the Margomulyo mangrove tourism area. The analysis used is a qualitative descriptive analysistechnique with a comparative method to compare the components of the development of the management of the margomulyo mangrove tourism area between existing conditions which include attraction, accessibility, amenity and,ancillary service, with the principles of community based tourism, namely social, economic and cultural in margomulyo mangrove tourism.